The Visual in Medieval Texts and Images (KULT_online, 2011)
In the Middle Ages, pictures tell stories, and texts open up visual spaces for their readers. Horst Wenzel’s most recent publication is dedicated to just such interactions between texts and images. Spiegelungen. Zur Kultur der Visualität im Mittelalter (Reflections: The Culture of Visuality in the Middle Ages) deals both with the gaze as it is inscribed within texts and images, and with the perception of these media, taking the culture of the court as a starting point. By systematising the techniques employed to guide perception, such as Appell and deixis, Wenzel examines the potential for visualisation inherent in medieval texts.